Effects of atropine on choroidal thickness in myopic children: a meta-analysis - Yang, Yaqi; Wei, Lijuan; Wang, Bo; Zheng, Wei (Frontiers in Pharmacology, 2024)
Background Atropine is an effective medicine for myopia prevention and control. This meta-analysis was conducted to investigate the effects of atropine on choroidal thickness (ChT) in children with myopia. Methods Between its inception and 1 June 2023, Medline, Embase, and Web of Science were all searched, and only English literature was included. The choroidal thickness was the primary study outcome. Axial length, standardized equivalent refraction were examined as secondary outcomes. STATA 12.0 was used for data extraction and analysis. Results A total of 307 eyes were involved in this study to evaluate the effect of atropine on ChT, axial length (AL) and standardized equivalent refraction (SER) in myopic children. Choroidal thickening was significantly higher in the atropine group than in the control group at 1 month (WMD, 6.87 mm, 95% CI, 0.04 to 13.10, P = 0.049), whereas it was significantly higher in the atropine group than in the control group at months 6 (WMD, 10.37 mm, 95% CI, −3.21 to 23.95, P = 0.135), 12 (WMD, 15.10 mm, 95% CI, −5.08 to 35.27, P = 0.143) and at final follow-up (WMD, 11.52 mm, 95% CI, −3.26 to 26.31, P = 0.127), the differences were not statistically significant. At months 1 (WMD, −0.03 mm, 95% CI, −0.04 to −0.01, P = 0.003), 6 (WMD, −0.07 mm, 95% CI, −0.01 to −0.03, P = 0.000), 12 (WMD, −0.13mm, 95% CI, −0.15 to −0.11, P = 0.843), and at final follow-up (WMD, −0.08 mm, 95% CI, −0.16 to −0.01, P = 0.127), atropine treatment was able to delay the axial elongation. At 1-month follow-up, there was no significant difference in the effect of atropine on SER in myopic children compared with the control group (WMD, 0.01D, 95% CI, −0.07 to 26.31, P = 0.127), whereas it was able to control the progression of refractive status at final follow-up (WMD, 11.52 mm, 95% CI, −3.26 to 26.31, P = 0.127). Conclusion Limited evidence suggests that 0.01% atropine causes choroidal thickening in myopic children at 1 month of treatment. In the short term, choroidal thickness may be a predictor of the effectiveness of atropine in controlling myopia in children. 0.01% atropine is effective in controlling myopic progression in terms of SER and AL. Systematic Review Registration http://www.crd.york.ac.uk/prospero, identifier, CRD42022381195.